“The Real Green” or Just Gimmick: The Implementation of Green Concept in Inagro’s Instagram - Tangguh Okta Wibowo; Satya Candrasari; Davis Roganda Parlindungan; Heppy New Year Haloho (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2022)
This research paper raises the issue of green marketing in content that usually has a figurative meaning or is also called an oxymoron because a green product is a product that is not produced through a fabrication process. However, this research explores if the product is indeed a product that comes from nature. In addition, this paper examines further the relationship between content publishing for a pro-environmental company, namely PT, Intidaya Agrolestari (Inagro), on its Instagram account @inagro.id. This research examines the application of green concept content on the @inagro.id account and its suitability with data in the field. The method used in this research is a virtual observation of the @inagro.id Instagram account, field observations, interviews, and documentation. The results show that if there are differences with previous research regarding green marketing, the company only used advertising to label its products as green products. With the help of a case study from Inagro, publishing content on the @inagro.id Instagram account is limited to only informing the products and services offered, including various facilities, atmosphere, and also nature-based educational packages. The implementation of the green concept has not been seen explicitly, even though the content has met the green criteria. Nevertheless, Inagro as a nature-based tourist destination has at least highlighted a green atmosphere and is not a gimmick. The content of the Instagram channel has been examined to determine whether it offers additional information through the Inagro case study, where the product being offered is one manufactured from nature. Images used to conceal products don't always serve to mislead the production process; instead, they encourage further discussion that isn't just centered on information about product for labeling green but also information that raising visitor awareness of concern for the environment.ABSTRAK Penelitian ini mengangkat isu green marketing dalam konten yang biasanya memiliki arti kiasan atau disebut juga oxymoron karena produk green merupakan produk yang tidak diproduksi melalui proses fabrikasi. Namun, penelitian ini mengeksplorasi jika produk dari perusahaan yang diteliti memang produk yang berasal dari alam. Selain itu, tulisan ini mengkaji lebih jauh hubungan antara penerbitan konten untuk perusahaan pro lingkungan yaitu PT Intidaya Agrolestari (Inagro), pada akun Instagram @inagro.id. Penelitian ini mengkaji penerapan konten konsep green pada akun @inagro.id dan kesesuaiannya dengan data di lapangan. Metode yang digunakan dalam penelitian ini adalah observasi virtual akun Instagram @inagro.id, observasi lapangan, wawancara, dan dokumentasi. Hasil penelitian menunjukkan jika terdapat perbedaan dengan penelitian sebelumnya mengenai green marketing yang dimanfaatkan perusahaan hanya memanfaatkan periklanan untuk melabeli produknya sebagai produk green. Dengan melalui studi kasus dari Inagro, penerbitan konten di akun Instagram @inagro.id terbatas hanya menginformasikan produk dan jasa yang ditawarkan, termasuk beragam fasilitas, atmosfer, dan juga paket edukasi berbasis alam. Penerapan konsep green belum terlihat secara eksplisit, meskipun di dalam kontennya telah memenuhi kriteria green. Meskipun demikian, Inagro sebagai tempat wisata berbasis alam setidaknya telah menonjolkan atmosfer yang green dan bukan merupakan gimik. Melalui studi kasus Inagro, konten yang dianalisis di channel Instagram menunjukkan jika mengandung informasi lain dan mengajak pada diskusi mengenai green lebih lanjut. Produk yang dikemas melalui gambar tidak selalu gambar yang menipu proses pembuatannya, melainkan mengundang diskusi lebih lanjut, tidak semata-mata terfokus pada informasi yang mempromosikan hijau, tetapi informasi yang meningkatkan kesadaran akan kepedulian lingkungan bagi pengunjung.